Vitrectomy for Symptomatic Asteroid Hyalosis. (September 2021) - Marlow, Elizabeth; Hassan, Tarek; Faia, Lisa; Drenser, Kimberly; Garretson, Bruce
Purpose: Acute vision loss may accompany complete or partial posterior vitreous separation in asteroid hyalosis (AH), and pars plana vitrectomy may resolve these symptoms. Methods: Six individuals with AH and acute vision loss associated with diagnosed posterior vitreous separation were treated with pars plana vitrectomy, and visual acuity (VA) recovery was monitored for 3 months. Results: The study patients' preoperative VA ranged from 20/25 to 20/2500 (mean, 20/150; logMAR, 0.88). The average decrease in VA with anterior progression of the hyaloid was logMAR 0.70. Following surgical clearance of the asteroid bodies, VA returned to baseline within 1 month following vitrectomy in 2 eyes, and within 3 months in all eyes. Final VA was 20/20 to 20/200 (mean, 20/35; logMAR, 0.24). Conclusions: Patients with AH may present with acute onset of severe vision loss in association with posterior vitreous separation. Vitrectomy may be curative and restore vision.